PENGARUH INVESTASI DAN PENDANAAN TERHADAP BIAYA MODAL PERUSAHAAN DAN FINANCIAL DISTRESS PERUSAHAAN TAMBANG BATUBARA YANG GO PUBLIC DI INDONESIA - LCA Robin Jonathan (RJABM (Research Journal of Accounting and Business Management), 2018)
The purpose of this study to analize and determine the effect of investment and funding to the cost of company capital and financial distress. The development of mining and mining service comnaies that go public today reached 42 companies in Indonesia in the period 2013-2015, including examined 23 financial statement of coal mining companies at the same time.Using regression path analysis methode to test the magnitude of the effect indicated by the path coefficient on each path diagram of the causal relationship between investment decision and funding decision as exogenous variable to cost of campany capital and financial distress as endogenous variable.The results showed that investment decisions and funding decisions significantly affect the cost of company capital; Investment decisions have a significant and dominant effect on financial distress and have a negative and insignificant effect on financial distress through the cost of company capital; Funding decisions have a negative and insignificant effect on financial distress and have a significant effect on financial distress through the cost of company capital; The cost of company capital has a negative and insignificant effect on financial distress.